Optimal Process Design and Sensitivity Analysis of Shell and Tube Heat Exchanger Operated with Nanofluids - Yahaya, Emmanuel (Curtin University, 2017)
This research project aims to conduct an optimal design of shell and tube heat exchanger operated with nanofluids using automated Kern’s method. The main objective function of this work is to reduce the total annual cost (covering capital investment and annual operating cost). Results from two case studies indicate that the employment of Al2O3 based nanofluids as heat transfer fluids reduce cost by 40.97% and 55.77%, respectively, compared to the original design with conventional fluids.